Psychometric properties and measurement invariance of a European Portuguese version of the fear of COVID-19 scale - Jarego, Margarida; Ferreira-Valente, Alexandra; Miguel Costa, Rui; Tavares, Mafalda; Pais-Ribeiro, José (Anales de Psicología / Annals of Psychology, 2023)
The novelty and uncertainty of the pandemic nourished a generalized fear of the COVID-19, which seems to have exacerbated the pandemic’s negative impact. It is thus relevant to monitor fear of COVID-19 and its association with individuals’ mental health, well-being, and behaviors. Valid and reliable measures of fear of COVID-19 are necessary for that purpose. This study aimed at assessing the psychometric properties of a European Portuguese version of the Fear of COVID-19 scale (FCV-19S-P). A secondary aim was to assess FCV-19S-P’s multigroup measurement invariance (female vs. male). A sample of 572 Portuguese adults (72 % female) completed the FCV-19S-P and measures of depression, anxiety, and stress. The study results supported this version validity and reliability (Cronbach’s alpha = .84; Composite Reliability = .83), and a factorial structure similar to the original version. Fear of COVID-19 was positively associated (.23 < r < .31) with depression, anxiety, and stress. Results of the multigroup invariance analysis supported the FCV-19S-P total scalar invariance and its partial residual invariance, suggesting that this measure may be used to reach valid conclusions in respect to gender comparisons in samples of Portuguese adults in regard to group observed composite means.